Incorporation of fluorophosphate in apatite. (1st May 2018) - Bollmeyer, Melissa M.; Yoder, Claude H.
Graphical abstract: Incorporation of the fluorophosphate ion in hydroxylapatite results in the formation of fluorapatite, which can be rationalized by displacement of channel hydroxide by the fluoride of fluorophosphate ion with coincident displacement of fluoride by hydroxide. Abstract: The fluorophosphate ion has been widely used as a source of fluoride in dentifrices because of its anticaries properties. Because it is isoelectronic with sulfate, which is known to replace phosphate in apatite, fluorophosphate could be expected to react similarly. In an attempt to incorporate the fluorophosphate ion into hydroxylapatite, calcium and strontium hydroxylapatites were synthesized in both aqueous and nonaqueous solutions in the presence of fluorophosphate. The corresponding fluorophosphate salts (CaFPO3 and SrFPO3 ) were also synthesized and found to decompose over time to their corresponding fluorapatites. Samples were characterized using solid state 19 F NMR, percent fluorine analysis, and unit cell parameter analysis. Hydrolysis of the fluorophosphate ion in various solutions was determined using solution 19 F NMR. The presence of hydroxylapatite or calcium ions in an aqueous solution of fluorophosphate at 80 °C and pH 7 or 9 resulted in significant hydrolysis. Inclusion of Na2 FPO3 as a reactant, along with calcium or strontium nitrate and sodium phosphate, produced only fluorapatite, a result of the hydrolysis of the FPO3 2− ion. With a larger ratio of fluorophosphate to phosphate and longer digestion times, the corresponding fluorophosphate salt (e.g., CaFPO3 ) formed in addition to the fluorapatite. Attempts to incorporate fluorophosphate into hydroxylapatite using nonaqueous solvents resulted in apatites with a larger weight percent of fluorine, but there was not sufficient evidence to conclude that the fluorophosphate ion was incorporated. The use of nonaqueous solvents, including DMSO, anisole, ethanol, several ionic liquids, 1:1 mixtures of anisole in glacial acetic acid, and 15-crown-5 ether in acetonitrile, produced apatite or fluorapatite with no evidence of incorporation of FPO3 . It is convenient to explain the failure of both aqueous and nonaqueous syntheses by assuming that the fluorophosphate ion, perhaps in an unstable apatite phase, serves to provide fluoride to the apatite channel while the displaced hydroxide reacts with the fluorophosphate to form phosphate for the formation of fluorapatite.